(untitled) (KULT_online, 2011)
In his thesis on The Beauty of the Beast Alexander van de Bergh focuses on the topic of love and partnership between humans and non-humans as a literary motif in English and American narrative prose. The book combines aspects of cultural and literary studies and narratological as well as socio-psychological approaches to the concept of ’love’ with the attempt to find clear categories for the figure of the non-human monstrous partner. However convincing this categorisation may be, under its anxious endeavouring for perfection the doctoral thesis tends to lack independent argumentation, and can therefore be considered symptomatic of the increasing standardisation of scientific methods and concepts.